Dog Diaries : Mission ImPAWsible - Patterson, James, 1947-; Butler, Steven, 1983-; Watson, Richard, 1980- (New York : Little, Brown and Company, 2020)
Juniors family goes on vacation without him and he gets into mischief at the kennel.
Accelerated Reader AR
Keywords: Dogs -- Juvenile fiction; Kennels -- Juvenile fiction; Juvenile fiction